Geology of a large intact extensional oceanic arc crustal section with superior exposures: Cretaceous Alisitos Arc, Baja California (Mexico) - Busby, Cathy J.; Morris, Rebecca A.; DeBari, Susan M.; Medynski, Sarah; Putirka, Keith D.; Andrews, Graham D. M.; Schmitt, Axel Karl; Brown, Sarah R. (Special papers / the Geological Society of America, 2023)
"The Rosario segment of the Cretaceous Alisitos arc represents an extensional oceanic arc with abundant silicic pyroclastic rocks, culminating in arc rifting with outpouring of mafic magmas. This book describes caldera collapse features, caldera plumbing systems, transition from plutons to eruptive products, pluton growth, products of deep-water mafic to silicic eruptions, and hot pyroclastic flow transformations"--